2021
DOI: 10.3389/fnsys.2021.688210
|View full text |Cite
|
Sign up to set email alerts
|

Neuropoly: An Educational Board Game to Facilitate Neurology Learning

Abstract: Introduction: Neurology is arguably one of the most difficult subjects to teach and study in the medical curriculum. Educational games (EG) may be a valid option to enhance motivation in neurology residents.Methods: We developed an educational board game (Neuropoly) to assist in teaching neurology. We present here an overview of the game, as well as the results of a pilot study aimed at determining: (a) the efficacy of the game in teaching certain neurological concepts; and (b) student compliance and satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The learning game Viral Hepatitis similarly demonstrated pre‐post test improvement in learning 4 . A recent study concerning the educational game, “Neuropoly” also reported pre‐post test learning gains 10 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The learning game Viral Hepatitis similarly demonstrated pre‐post test improvement in learning 4 . A recent study concerning the educational game, “Neuropoly” also reported pre‐post test learning gains 10 …”
Section: Discussionmentioning
confidence: 85%
“…4 A recent study concerning the educational game, "Neuropoly" also reported pre-post test learning gains. 10 Studies have shown that students enjoy playing games and continue to discuss them after the game is over. 11 Things learned from the game can be applied to various clinical situations including diagnosis, management, problem-solving, communication, and teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…It showed a benefit in short-term memorization but was not able to prove its efficacy in long-term memory. (16) And, "Neuropoly" is a board game to enhance the neurological semiology abilities of neurology residents, although it is a viable and inexpensive approach to target neurophobia (17) , all the games we found in this review are, except for the virtual simulation for the diagnosis of subarachnoid hemorrhage (13) , in person and made of physical materials. Hence, we found a lack of technological and digital solutions to aid in traditional neurological semiology teaching.…”
Section: Resultsmentioning
confidence: 99%
“…Craving has also been implicated in IGD, and the presence of gaming cues may be difficult to avoid, given how individuals currently use digital devices. Furthermore, games have been used for educational purposes, with schools incorporating games to promote learning . Internet gaming may improve visuospatial ability and motor skills and may promote well-being.…”
Section: Introductionmentioning
confidence: 99%